(untitled) (Albayan Scientific Journal, 2023)
This research work study the a projectiles motion without air resistance and projectiles motion with air resistance by using vector-valued function. We consider two-dimensional motion of a projectile experiencing a constant gravitational force in the projectile’s speed and look at launching projectiles, as well as how varying initial velocity and height affect the launch angle. Finally, we add air resistance to the projectile problem and compare two different models: air resistance proportional to the projectile’s velocity and air resistance proportional to velocity squared We find that :The equations of motions are coupled nonlinear equations. Their solutions have general properties which are easily visualized, although much different from those obtained when an air resistance is neglected.